Effect of different current types on the microstructure of electrodeposited aluminium coatings - TENG Xinyue; LIU Chaonan; ZHANG Dongxun; WANG Zhenwei; WEN Feng (He jishu)
BackgroundTritium permeation leakage exists in fusion reactor such as International Thermonuclear Experimental Reactor (ITER), which leads to a series of problems such as fuel loss and environmental pollution, etc. Al2O3 coating is a hot research topic for preventing tritium permeation. The preparation of Al2O3 coatings on the surface of materials is an effective way to solve this problem. Electrodeposition of Al and heat treatment diffusion technology is a common method to prepare tritium-resistant coatings. The relevant parameters during the preparation process have important effects on the microstructure and tritium-resistant performance of Al coatings.PurposeThis study aims to analyse the mechanism of the effect of different electrodeposition process parameters on the phase structure and internal micro-morphology of aluminium coatings, and to obtain good quality aluminum coatings.MethodsFirstly, the aluminum coating was prepared on the surface of 316L stainless steel substrate at room temperature with 316L stainless steel as cathode, aluminum wire (99.99% purity) as anode, and AlCl3-1-Ethyl-3-methylimidazolium Chloride (EMIC) ionic liquid as plating solution. Then, the changes of surface and cross section morphology of aluminum coating were observed by changing the current density under direct current mode whilst the plating time (60 min) was fixed, and the difference of the microstructure of the aluminum coating prepared under the three current modes, i.e., direct current (15 mA·cm-2), unidirectional pulse and bidirectional pulse current, was compared. Both the X-ray diffraction (XRD) and scanning electron microscopy (SEM) were employed to characterize the phase structure and internal microstructure of aluminum coatings.ResultsThe experimental results show that the coatings are all composed of Al element and have a face-centered cubic structure, in which the preferred orientation of the crystal faces of the direct current and bidirectional pulsed electrodeposition coatings is different. In the direct current mode, some grains on the coating surface increase with the increase of direct current density, and the optimal current density of direct current electrodeposition ranges from 10~20 mA·cm-2. Compared with the direct current electrodeposition process with similar parameters, under the condition of the same current density and electroplating time, the grain size of the coating microstructure obtained by pulsed current and bidirectional pulse electrodeposition is more uniform, and the grain size after bidirectional pulse electrodeposition is smaller, and the thickness of the aluminum coating obtained by unidirectional pulse current waveform electrodeposition is the largest. The grain and thickness of aluminum coating formed by bidirectional pulse current are the smallest and the grain size is uniform.ConclusionsThe introduction of pulse current has a significant effect on the size and uniformity of particles on the surface of aluminum coating. The coating obtained by pulse current is relatively dense, the grain thinning phenomenon is obvious, and the grain size is relatively uniform. The reason is that the large instantaneous peak current can inhibit the excessive growth of the grain and play a leveling role, so as to further improve the micro-morphology of the coating and improve the quality of the coating.